Diversity of Plant Visiting Insects of Intercrop Lantana camara in Oil Palm Plantation - Rizki Putri Amelia; Chandra Irsan (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2023)
Refugia plant flowers can be a support for biological pest control applications. Insects are visitors to flowering plants, especially the Lantana camara plant, which is interesting to study. This study aimed to determine the diversity of insects that visit flower plants planted among oil palm plants. This study used the Scan Sampling method or direct observation. Insects found in L. camara plants were collected and identified. The results showed that there were 11 species belonging to 11 families and 7 orders. The index value of the diversity of attack species from L. camara flower plants was low. Which means L. camara flowers are not attractive to insects. The species evenness index and dominance index ranged from 0.31-0.60 which means moderate dominance. The dominant insect found in L. camara flowers is Bothrogonia addita. In L. camara flower plants planted among oil palm plants, 11 species of arthropods belonging to 11 families and 7 orders were found. The 11 species are O. salticus, A. coquebertii, B. tabaci, B. addita, Componotus sp., H. itama, A. violae, C. gemmatus, I. elegans, A. crenulate, L. marginicollis. Insects that came to L. camara flowers in the morning were more than those that came in the afternoon with a successive number of 11 species, 268 individuals and 9 species, 141 individuals. The dominant insect found in L. camara flowers is B. addita.